Amra korbo joy: a self-sustaining business model for entrepreneurs with profitability, responsibility and visibility of Nescafé - Khan, Md. Ashraful Hassan (BRAC University, 2014)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2014.